Interdepartmental conflict in large enterprises in South Africa: A survey - B. J. Bloch (South African Journal of Business Management, 1987)
Managerial literature has always tended to underrate the significance of the horizontal or lateral dimension of organizations. The rationale for this paper is the increasing importance of lateral interdepartmental relationships as business enterprises increase in size and complexity. The aim of this investigation is to determine the extent to which interdepartmental conflict prevails, and the nature of the causes thereof, in large enterprises in South Africa. The investigation was conducted by means of a mail survey of manufacturing enterprises with in excess of 300 employees. A questionnaire composed of 24 multiple-choice items was sent to 900 manufacturing enterprises. A total of 282 usable responses was obtained. Responses indicate that enterprises in the sample generally experience moderate to high levels of interdepartmental conflict. The results indicate that the level of interdepartmental conflict does not differ statistically with respect to size of enterprise, geographic location or the nature of the responding department. The breakdown of responses suggests that production and marketing departments play a dominant role in the interdepartmental scenario, with finance and personnel taking a secondary role.
Keywords: 650